On the nonlinear relation between product market competition and earnings quality. Issue 7 (10th November 2019) - Guo, Ying; Jung, Boochun; Yang, Yanhua Sunny
Abstract : The literature documents conflicting results regarding the influence of product market competition on earnings quality. We extend this stream of literature by incorporating competition's effect on both the opportunities and the incentives to manage earnings. The combination of both effects results in a nonlinear relation between product market competition and earnings quality. At low competition levels, additional information associated with one more rival helps reveal earnings irregularity and deter earnings management to a larger extent than its effect on the incentives to manage earnings, suggesting a positive relation between competition and earnings quality. At high competition levels, the latter effect dominates the former. We thus predict a positive (negative) relation between competition and earnings quality at low (high) competition levels. Consistent with our hypothesis, we document an inverted U-shaped relation between earnings quality and product market competition.